On developing responsible leaders. Issue 6 (11th June 2018) - Eriksen, Matthew; Cooper, Kevin
Abstract : Purpose: The purpose of this paper is to present a methodology to develop responsible leaders through developing their response-ability within the context of their day-to-day lives that addresses the existing disconnect between the knowledge about responsible leadership and its practice. Design/methodology/approach: The responsible leadership development methodology begins by helping individuals increase their awareness of their impact on others based on how they are relating and responding to them. This is facilitated through individuals engaging in self-reflexivity and reflection on relationships for which they want to be responsible. Then individuals experiment with and take responsibility for how they are relating and responding within the relationships. Finally, they engage in self-reflexivity and reflection to make sense of the experience to develop practical wisdom and the response-ability that will allow them to become more responsible leaders. Findings: Students that completed an MBA leadership course that employed the responsible leadership development methodology overwhelmingly reported that their response-ability improved in ways that allowed them to become more responsible for their actions, impact on others, relationships and the reality they co-construct with others, as well as becoming a more responsible person. Research limitations/implications: The research is based on an MBA class of 24 students, only a few of whom currently occupied organizational leadership positions. Originality/value: The presented leadership development methodology facilitates the development of responsible leaders through developing their ability and commitment to act responsibly within the context of their day-to-day lives.